Pengembangan Development of coastal tourism in Central Buton Regency: (Studies on Mutiara, Wantopi, and Katembe): Bahasa Indonesia - La Bonto, Ahmad Zulkivar; Rofiaty, Roafiaty; Susilowati, Christin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
This study aims to explore the problems and find strategies for developing beach tourism in ButonTengah Regency, namely Mutiara beach tourism in Gumanano village, Wantopi beach tourism in Wantopi village, and Katembe beach tourism in Madongka village. This research is a qualitative research with a case study approach.This research was conducted on ten informants who were representatives of beach tourism stakeholders in each of these tourist destinations, consisting of the Department of Youth and Tourism of Buton Tengah Regency, the Village Head of each village, the community, and tourists. The results of the study revealed that the Buton Tengah Regency currently has tourism resources, including natural resources, as well as heritage and culture, but there were still problems in the management of tourism. Problems found include the lack of supporting factors for tourism, destination management and destination management of the organization that was not well organized, and there were no guarantees for security and safety for tourists. From these problems found strategies in tourism management including the need for training of stakeholder groups, the need to create regulations and involve all stakeholders in tourism management, and immediately issued a local regulation governing tourism management in Buton Tengah Regency.